Tales of Butler County: Providence - Belinda Larsen (Symphony in the Flint Hills, 2018)
Introduction: Where was Providence? The Kansas prairie was home to many towns, villages, and settlements which have long passed away and been forgotten. Butler County had a number of such towns, many of which were oil towns with schools, churches, and businesses. (Originally published in The Butler County Times-Gazette, June 11 & 13, 2015.)